KNOWLEDGE, ATTITUDE, AND PRACTICE OF ANTIBIOTIC USE IN CHILDREN ATTENDING OUTPATIENT DEPARTMENTS IN INDIA: A CROSS-SECTIONAL STUDY - Mathew, Merly Ann; A, Prasananjali; R, Ram Mohan; MD, Vidhyashree; Murugan, Arun; Ramasubramanian; G, Pavithra; K, Sathishkumar (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2025)
Background: In the pediatric population, parental views frequently result in antibiotic misuse and illogical use. Purpose: To ascertain the knowledge, attitudes, and practices of parents with relation to the use of antibiotics in their children. Methods: A cross-sectional study of mothers visiting the pediatric outpatient department at the Government Medical College and Hospital in Chennai's Omandurar Government Estate was carried out during August and September of 2022. A standardized questionnaire that was given by the interviewer was used to gather data. Excel was used to chart the data and express them as descriptive data. Results: Mean age of the mothers who participated in the study was 25.2 ± 9.1 years. About more than half (56%) of the participants didn’t know about antibiotic use. Almost 73% of the participants give antibiotics if their child has fever without consulting a doctor. More than half (63%) of the participants have accepted that they do not fully complete the number of days of the course of antibiotic recommended by their pediatrician if their child feels better. The practice of reusing stored antibiotics from their previous prescription is prevalent up to 82%. Around 98% do demand to have an antibiotic if their child has fever and an equal proportion 93% of participants want to give antibiotics if their child has a sore throat. Conclusion: Approximately 74% of mothers receive antibiotics without a prescription, albeit at different frequencies. Our research suggested that parents may benefit from knowledge-based education initiatives.